Effects of initial leaching for estimates of mass loss and microbial decomposition—Call for an increased nuance. Issue 8 (31st July 2022) - Lind, Lovisa; Harbicht, Andrew; Bergman, Eva; Edwartz, Johannes; Eckstein, Rolf Lutz
Abstract: Decomposition is essential to carbon, nutrient, and energy cycling among and within ecosystems. Several methods have been proposed for studying litter decomposition by using a standardized and commercially available substrate. One of these methods is the Tea Bag Index (TBI) which uses tea bags (green and rooibos tea) incubated for 90 days. The TBI is now applied all over the globe, but despite its usefulness and wide application, the TBI (as well as other methods) does not explicitly account for the differences in potential loss of litter mass due to initial leaching in habitats with large differences in moisture. We, therefore, studied the short‐term mass losses (3–4 h) due to initial leaching under field and laboratory conditions for green and rooibos tea using the TBI and contextualized our findings using existing long‐term mass loss (90 days) in the field for both aquatic and terrestrial environments. For both tea litter types, we found a fast initial leaching rate, which could be mistaken for decomposition through microbial activity. This initial leaching was higher than the hydrolyzable fraction given in the description of the TBI. We also found that leaching increased with increasing temperature and that leaching in terrestrial environments with high soil moisture (>90%) is almost as large as in aquatic environments. When comparing our findings to long‐term studies, we found that up to 30–50% of the mass loss of green tea reported as decomposition could be lost through leaching alone in high moisture environments (>90% soil moisture and submerged). Not accounting for such differences in initial leaching across habitats may lead to a systematic overestimation of the microbial decomposition in wet habitats. Future studies of microbial decomposition should adjust their methods depending on the habitat, and clearly specify the type of decomposition that the study focuses on. Abstract : We found that both rooibos and green tea experienced a fast initial leaching rate, which eventually reached an asymptotic maximum. When comparing findings from our short‐term study to our to long‐term studies we found that up to 30‐50% of the mass loss reported as decomposition of green tea, could be lost through leaching alone in high moisture environments. Hence, not accounting for initial leaching will lead to a systematic overestimation of microbial decomposition and thus produce erroneous results when directly using mass loss values.